The Population Pharmacokinetics of Meropenem in Adult Patients With Rifampicin-Sensitive Pulmonary Tuberculosis - Abulfathi, Ahmed A.; de Jager, Veronique; van Brakel, Elana; Reuter, Helmuth; Gupte, Nikhil; Vanker, Naadira; Barnes, Grace L.; Nuermberger, Eric; Dorman, Susan E.; Diacon, Andreas H.; Dooley, Kelly E.; Svensson, Elin M. (Frontiers in Pharmacology, 2021)
Background Meropenem is being investigated for repurposing as an anti-tuberculosis drug. This study aimed to develop a meropenem population pharmacokinetics model in patients with pulmonary tuberculosis and identify covariates explaining inter-individual variability. Methods Patients were randomized to one of four treatment groups: meropenem 2g thrice daily plus oral rifampicin 20 mg/kg once daily, meropenem 2g thrice daily, meropenem 1g thrice daily, and meropenem 3g once daily. Meropenem was administered by intravenous infusion over 0.5-1h. All patients also received oral amoxicillin/clavulanate together with each meropenem dose, and treatments continued daily for 14 days. Intensive plasma pharmacokinetics sampling over 8h was conducted on 14th day of the study. Nonlinear mixed-effects modelling was used for data analysis. The best model was chosen based on likelihood metrics, goodness-of-fit plots and parsimony. Covariates were tested stepwise. Results A total of 404 concentration measurements from 49 patients were included in the analysis. A 2-compartment model parameterized with clearance (CL), inter-compartmental clearance (Q), central (V1) and peripheral (V2) volumes of distribution fitted the data well. Typical values of CL, Q, V1 and V2 were 11.8 L/h, 3.26 L/h, 14.2 L, and 3.12 L, respectively. The relative standard errors of the parameter estimates ranged from 3.8 to 35.4%. The covariate relations included in the final model were creatinine clearance on CL, and allometric scaling with body weight on all disposition parameters. An effect of age on CL as previously reported could not be identified. Conclusion A 2-compartment model described meropenem population pharmacokinetics in patients with pulmonary tuberculosis well. Covariates found to improve model fit were creatinine clearance and body weight but not rifampicin treatment. The final model will be used for an integrated pharmacokinetics/pharmacodynamics analysis linking meropenem exposure to early bactericidal activity.